Estimation of Forest Biomass and Carbon Stocks Changes in Sunt (Acacia nilotica Linn Willd.) Plantations, Sinnar State, Sudan - Abubakr A. A. Osman; Brolly Gabor; Kiraly Geza (Journal of Sylva Indonesiana, 2026)
This study quantifies changes in tree density, above ground biomass (AGB) and above ground carbon (AGC) in Seiro Riverine Forests (SRF) and Abutiga Riverine Forest (ARF)we use inventory data done by forest national corporation (FNC) in 2006 and reinventors in 2015for this research. A total of 224 circular sample plots (1000 m² each), 129 in Seiro and 96 in Abutiga, were established using a systematic sampling grid method. The distance between plots was 100 m, and between survey lines, 200 m. In each plot, all living trees were identified and counted, and their diameters at breast height (DBH) were recorded. The findings revealed a significant reduction in average tree density, dropping from 93 to 40 trees/ha in SRF, and from 140 to 40 trees/ha in ARF. (AGB) and (AGC) were assessed in Acacia nilotica plantations of varying ages in Abutiga and Seiro forests. Garef consistently showed the highest biomass and carbon stocks, Maya the lowest, and Karb intermediate values. Similar trends were observed across older and younger stands, highlighting strong site-specific differences. These results emphasize the importance of targeted management to sustain carbon storage and enhance the ecological function of Acacia nilotica plantations.